Enabling (e)motion - Linnea Bågander; Karolin Kent (Dance Articulated, 2020)
This article discusses a practical exploration of the ability of a textile to meet with and affect bodies. It builds on the inherent ability of textiles, particularly in the form of a garment, to evoke movements and emotions. This paper suggests a shift in focus of the design of bodily materiality, towards an expression emerging from interactions connecting materiality and performativity. The findings are the result of 2.5 years of exploration, during which four performances, ten workshops, and four exhibitions were performed. The entwined parameters of expressing and informing are applied as a material choreographic thinking, which in this case results in a material choreography of openness, where expressing and informing are essential as entwined design parameters in the design of body-material interactions. The material choreography is developed as a method for addressing somatic experience, with improvements in terms of wellbeing and presence as aesthetic goals, focusing on reducing movements and emotions relating to stress for people suffering from chronic fatigue syndrome.